The management of non-valvular atrial fibrillation (NVAF) in Australian general practice: bridging the evidence-practice gap. A national, representative postal survey - Middleton Sandy; Zwar Nicholas A; Worthington John M; Gattellari Melina (BMC Family Practice, 2008)
Abstract Background General practitioners (GPs) are ideally placed to bridge the widely noted evidence-practice gap between current management of NVAF and the need to increase anticoagulant use to reduce the risk of fatal and disabling stroke in NVAF. We aimed to identify gaps in current care, and asked GPs to identify potentially useful strategies to overcome barriers to best practice. Methods We obtained contact details for a random sample of 1000 GPs from a national commercial data-base. Randomly selected GPs were mailed a questionnaire after an advance letter. Standardised reminders were administered to enhance response rates. As part of a larger survey assessing GP management of NVAF, we included questions to explore GPs' risk assessment, estimates of stroke risk and GPs' perceptions of the risks and benefits of anticoagulation with warfarin. In addition, we explored GPs' perceived barriers to the wider uptake of anticoagulation, quality control of anticoagulation and their assessment of strategies to assist in managing NVAF. Results 596 out of 924 eligible GPs responded (64.4% response rate). The majority of GPs recognised that the benefits of warfarin outweighed the risks for three case scenarios in which warfarin is recommended according to Australian guidelines. In response to a hypothetical case scenario describing a patient with a supratherapeutic INR level of 5, 41.4% of the 596 GPs (n = 247) and 22.0% (n = 131) would be "highly likely" or "likely", respectively, to cease warfarin therapy and resume at a lower dose when INR levels are within therapeutic range. Only 27.9% (n = 166/596) would reassess the patient's INR levels within one day of recording the supratherapeutic INR. Patient contraindications to warfarin was reported to "usually" or "always" apply to the patients of 40.6% (n = 242/596) of GPs when considering whether or not to prescribe warfarin. Patient refusal to take warfarin "usually" or "always" applied to the patients of 22.3% (n = 133/596) of GPs. When asked to indicate the usefulness of strategies to assist in managing NVAF, the majority of GPs (89.1%, n = 531/596) reported that they would find patient educational resources outlining the benefits and risks of available treatments "quite useful" or "very useful". Just under two-thirds (65.2%; n = 389/596) reported that they would find point of care INR testing "quite" or "very" useful. An outreach specialist service and training to enable GPs to practice stroke medicine as a special interest were also considered to be "quite" or "very useful" by 61.9% (n = 369/596) GPs. Conclusion This survey identified gaps, based on GP self-report, in the current care of NVAF. GPs themselves have provided guidance on the selection of implementation strategies to bridge these gaps. These results may inform future initiatives designed to reduce the risk of fatal and disabling stroke in NVAF.